Cancer Drug Resistance - Teicher, Beverly A.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2006)
As genomic techniques gradually reveal the ability of malignant cells to respond to chemical and biological insults with remarkable flexibility of phenotype, it becomes clear that much remains to be done to control and eliminate such cells. In Cancer Drug Resistance, leading scientists from the best academic institutions and industrial laboratories summarize and synthesize the latest discoveries concerning the changes that occur in tumor cells as they develop resistance to a wide variety of anticancer therapeutics, as well as suggest new approaches to the biology of drug resistance that may afford new therapeutic opportunities. The authors review physiological resistance based tumor architecture, cellular resistance based on drug transport, epigenetic changes that neutralize or bypass drug cytotoxicity, and genetic changes that alter drug target molecules by decreasing or eliminating drug binding and efficacy. Highlights include new insights into resistance to antiangiogenic therapies, oncogenes and tumor suppressor genes in therapeutic resistance, cancer stem cells, and the development of more effective therapies. There are also new findings on tumor immune escape mechanisms, gene amplification in drug resistance, the molecular determinants of multidrug resistance, and resistance to taxanes and Herceptin®. Authoritative and insightful, Cancer Drug Resistance offers basic and clinical investigators a state-of-the-art synthesis of the many faceted research now available on the biology and genetics of tumor resistance, as well as exciting new approaches to its prevention and eradication.
Physiological Resistance -- The Cycle Between Angiogenesis, Perfusion, and Hypoxia in Tumors -- Influence of Tumor pH on Therapeutic Response -- Tumor Oxygenation and Treatment Response -- Oncogenes and Tumor Suppressor Genes in Therapeutic Resistance -- PET Imaging of Response and Resistance to Cancer Therapy -- Biological Resistance -- Cancer Stem Cells Implications for Development of More Effective Therapies -- Therapeutic Resistance in Leukemia -- Tumor Site Implantation and Animal Model Selection in Oncology -- In Vivo Resistance -- Characteristics of the Metastatic Phenotype -- The Microenvironment and Drug Resistance -- Biochemical Resistance -- Glutathione and Glutathione S-Transferases in Drug Resistance -- Metallothioneins in Drug Resistance -- Molecular Determinants of Intrinsic Multidrug Resistance in Cancer Cells and Tumors -- New and Revised Concepts in Multidrug Resistance -- Cisplatin Resistance -- Regulation of the Cellular Pharmacology and Cytotoxicity of Cisplatin by Copper Transporters -- Resistance To Taxanes -- CpG Island Methylation and Drug Resistance -- De Novo and Acquired Resistance to Antitumor Alkylating Agents -- Resistance to Antiangiogenic Agents -- The Role of Hormones, Growth Factors, and Oncogenes -- Resistance to Antiestrogens -- Mechanisms of Glucocorticoid Actions and Resistance in Multiple Myeloma -- Herceptin Resistance -- Role of TGF-? in Tumor Progression and Metastasis -- p53-Based Immunotherapy of Cancer -- Response and Resistance to Ionizing Radiation -- Amplification in DNA Copy Numbers as a Mechanism of Acquired Drug Resistance -- Clinical Aspects of Resistance -- Cancer Chemotherapy -- Molecular Profiling in Breast Cancer -- Tumor Immune Escape Mechanisms.
Keywords: Oncology .; Oncology